Exercise intervention and improvement of negative emotions in children: a meta-analysis - Jiayu Li; Xiaoping Jiang; Zan Huang; Tianyi Shao (BMC, 2023)
Abstract Background Anxiety, depression, and stress are the most common mental health problems in childhood. Exercise interventions in childhood help to promote mental health. Objective To investigate the relationship between exercise interventions and improvement of negative emotions such as anxiety, depression, and stress in children (5-12 years). Methods Articles were searched in five electronic databases from their inception to January 2023. The meta-analysis was performed using Stata 16.0. Results Twenty-three intervention studies included 6830 children. 1) The exercise intervention group was significantly better than the control group in improving negative emotions (Standard Mean Difference SMD=-0.25, 95% Confidence Intervals CI: -0.34 to -0.15, P < 0.01). Exercise intervention improved different kinds of negative emotions: anxiety (SMD=-0.19, 95% CI: -0.33 to -0.06, P < 0.01), depression (SMD=-0.22, 95% CI: -0.43 to -0.01, P < 0.01), and stress (SMD=-0.33, 95% CI: -0.53 to -0.14, P < 0.01); it was most effective at relieving problematic stress. Exercise interventions lasting 20-45 min were most effective in improving children's negative emotions (SMD=-0.38, 95% CI: -0.56 to -0.20, P < 0.01). An exercise intervention period of 10 weeks was more effective in improving children's negative mood (SMD=-0.26, 95% CI: -0.34 to -0.17, P = 0.274). Conclusion Exercise interventions may improve negative emotions such as anxiety, depression, and stress in children. These findings may have clinical implications for children with negative affect. However, these studies showed a large heterogeneity, and the results should be interpreted with caution. Future studies should report the variability of exercise interventions by gender, age group, and type, intensity, and place of exercise.